Central diabetes insipidus following immunization with BNT162b2 mRNA COVID-19 vaccine: a case report - Bouça, Bruno (2022)
Introduction: Cases of central diabetes insipidus (CDI) have been reported after COVID-19 infection, with hypophysitis being the most likely cause. COVID-19 vaccines' potential adverse effects may mimetize some of these complications. Case report: Woman 37 years old, with rheumatoid arthritis under adalimumab (40 mg twice a month) since December 2018. She was in her usual state of health when she received the second dose of the BNT162b2 mRNA COVID-19 vaccine (June 2021). Seven days later, she started reporting intense thirst and polyuria and consulted her family physician. Blood analysis: creatinine 0.7 mg/dL, glucose 95mg/dL, Na+ 141mEq/L, K+ 3.9 mEq/L, TSH 3.8 mcUI/L (0.38-5.33), FT4 0.9 ng/dL (0.6-1.1), cortisol 215.4 nmol/L (185-624), ACTH 21.9 pg/mL (6- 48), FSH 4.76 UI/L, LH5.62 UI/L, estradiol 323 pmol/L, IGF1 74.8 ng/mL (88-209), PRL 24.7mcg/L (3.3-26.7) osmolality 298.2 mOs/Kg (250- 325); Urine analysis: volume 10200 mL/24h, osmolality 75 mOs/Kg (300-900), density 1.002. On water restriction test: 0' - Serum osmolality 308.8mOsm/Kg vs. urine osmolality 61.0 mOsm/Kg; 60' - urine osmolality 102 mOsm/Kg; urine osmolality 1 h after desmopressine was 511mOsm/kg. MRI revealed no abnormal signs consistent with hypophysitis except for the loss of the posterior pituitary bright spot on T1 weighted imaging. Diagnosis of CDI was assumed and started therapy with desmopressine. A report of potential adverse effects was addressed to national health authorities. Conclusion: In hypophysitis, MRI often shows loss of posterior pituitary bright spot on T1 weighted imaging, pituitary enlargement, or stalk thickening but those findings were not present in this patient. To the best of our knowledge, CDI has never been reported following the administration of a COVID-19 vaccine.